Reconstructions using alloys and ceramics - Gonçalves, S. E.P. [UNESP]; Bresciani, E. [UNESP] (Elsevier, 2017)
Different materials are used in prosthetic dental reconstructions: metals, ceramics, resins, and possible combinations thereof. The literature shows that esthetic demands by patients directed the current clinical practice toward metal-free reconstructions, despite the advantages of metallic restorations in terms of required dental reduction, fracture resistance, adaptation, and polishing properties. Prosthetic crowns still present the greatest challenge in terms of their maintenance in one of the most challenging environments: the oral environment. This environment is characterized by 100% relative humidity, heterogeneous composition of saliva, and individual variability; presence of widely variable and offensive microorganisms; influence of dietary habits and host characteristics; and presence of occlusal stresses due to masticatory forces in various directions and intensities. The knowledge of biology, mechanics, function, and esthetics of sound/intact teeth is an essential requisite to researchers seeking new restorative materials. Materials engineering present a key role in finding viable alternatives according to mechanical, esthetic, and economic aspects.
Keywords: Alloys; Cements; Ceramics; Oral environment; Tooth implant